Multi-criteria assessment of cyclability of roads in Montes Claros, MG, Brazil - Lopes, Rafael Aparecido Pereira; Santos Neto, Narciso Ferreira dos (National Journal of City Management, 2024)
This study investigated the cycling infrastructure and cyclists’ perceptions of sustainable urban mobility in Montes Claros, Minas Gerais, Brazil, based on bicycle use. The methodology involved an analysis of the road environment for cyclists and the application of questionnaires to experts and cyclists, using a multi-criteria approach. The results revealed limitations in the infrastructure, such as the lack of segregated bike lanes. Additionally, cyclists expressed concerns about safety, such as disrespect from drivers and insufficient lighting on roads. These findings highlight the need for investments in cycling infrastructure and public policies focused on safety and sustainable mobility. This study contributes to the knowledge of cyclability in Montes Claros by developing a procedure for cyclability analysis that can be used in other locations. Furthermore, it provides valuable information for urban planning and the promotion of bicycle use as a sustainable mode of transportation, with the potential to improve urban mobility and quality of life for the population.